Thorium utilization with pebble mixing system in fluoride salt-cooled High Temperature Reactor. (July 2019) - Zhu, Guifeng; Liu, Sijia; Zou, Yang; Yan, Rui; Tan, Menglu; Kang, Xuzong; Li, Minghai; Zhou, Bo; Dai, Ye
Abstract: Mixing system of uranium pebbles and thorium pebbles is compared with thorium blanket system to utilize thorium in Pebble Bed Fluoride Salt-cooled High Temperature Reactor (PB-FHR). A random modeling method is introduced to simulate the pebble mixing system. Cases with different volume fractions of uranium pebbles are researched to find the optimal utilization of uranium and the lower power nonuniformity. It indicates that using thorium in pebble mixing system with 80 vol% uranium pebbles can improve uranium utilization by 10%, while in thorium blanket system it can be increased by 20%. The radial power peak factor in pebble mixing system is about 1.48 while in thorium blanket system is about 1.83. In-pile residence time of thorium pebbles in pebble mixing system is only 4.7 year, while in thorium blanket system is 9 year. Thorium utilization with pebble mixing system in PB-FHR shows a little lower fuel utilization but higher safety and technical feasibility. Highlights: Pseudorandom distribution models of different pebbles are successfully established. We find the optimal utilization of uranium under 80 vol% uranium pebble. The radial power peak factor and in-pile residence time of thorium pebble significantly decrease in pebble mixing system.